Enhanced strains of Nb-doped BNKT-4ST piezoelectric ceramics via phase boundary and domain design. Issue 17 (1st September 2021) - Sun, Xiaoyuan; Liu, Zixuan; Qian, Hao; Liu, Yunfei; Lyu, Yinong
Abstract: A strategy that constructs the morphotropic phase boundary and manipulates the domain structure has been used to design the component of 0.96[Bi0.5 (Na0.84 K0.16 )0.5 Ti(1- x ) Nb x O3 ]-0.04SrTiO3 (BNKT-4ST-100 x Nb) to enhance the strain properties for actuator application. Non-equivalent Nb 5+ donor doping modulates the phase transition from the mixture of rhombohedral and tetragonal phases to the pseudocubic phase and results in the coexistence of multiple phases. Moreover, the high-resolution TEM confirms the existence of polar nano regions that contribute to the macroscopic relaxor behaviour. The size of the domains is reduced with increasing Nb 5+, resulting in an enhanced relaxor behaviour. The ferroelectric-relaxor transition temperature decreases from 85 to below 30 °C, implying a non-ergodic to ergodic relaxor transition. An improved strain of 0.56% and a giant normalized strain of 1120 pm/V were achieved for BNKT-4ST-1.5Nb, which were attributed to the unique domain structure in which nanodomains are embedded in an undistorted cubic matrix. Ferroelectric, antiferroelectric, and relaxor phases coexist. As the electric field is large enough, a reversible phase transition occurs. Furthermore, good temperature stability was obtained due to the stability of the nanodomains, and no degradation in strains was observed even after 10 4 cycles, which may originate from the reversible phase transition and dynamic domain wall. The results show that this design strategy offers a reference way to improve the strain behaviour and that BNKT-4ST-100 x Nb ceramics could be a potential material for high-displacement actuator applications.